Getting a Grip on the Handgrip Task: Handgrip Duration Correlates with Neuroticism But Not Conscientiousness - Goldberg, Simon B.; Flook, Lisa; Hirshberg, Matthew J.; Findley, David; Kesebir, Pelin; Schaefer, Stacey M.; Davidson, Richard J. (Frontiers in Psychology, 2017)
Questions regarding the replicability of key findings in the self-regulation literature (e.g., ego-depletion effect) have led some to call for a more thorough evaluation of commonly used measures of self-control. The isometric handgrip task is one such measure. The current study examined correlates of handgrip persistence using data drawn from a larger randomized controlled trial. Handgrip persistence was measured both at baseline and following a physical stressor (cold pressor test). Correlations were examined between handgrip performance and personality traits theoretically closely linked with self-regulation: conscientiousness and neuroticism. Baseline handgrip performance was correlated with several measures drawn from the nomological network of self-regulation including measures of trait neuroticism, mindfulness, anxiety sensitivity, perceived stress, and positive affect, although not with trait conscientiousness. Baseline handgrip predicted aversiveness experienced during the physical stressor, while changes in handgrip performance tracked changes in implicit and explicit negative affect (i.e., affective reactivity). These associations were largely maintained when controlling for variables highly correlated with overall grip strength (i.e., gender, height, and weight), although correlations separated by gender suggest associations were primarily driven by female participants. Results support future research using the handgrip task.